THE COORDINATED SOLUTION OF TWO DIFFERENTIAL EQUATIONS IN PRIVATE DERIVATIVES OF THE THIRD ORDER - Zh.N. Tasmambetov; N. Rajabov; Zh.K.Ubayeva (Academic Scientific Journal of Computer Science, 2019)
In the study the possibility of constructing a solution near a variety of special features of the system consisting of two differential equations in partial derivatives of the third order was investigated. There definitive aspects of such systems in comparison with systems consisting of two differential equations in partial derivatives of second order were established. The classification of regular and irregular singularities was carried out, the relevant solutions are constructed. A specific example shows that the application of the Frobenius - Latysheva method to the construction of a solution of a degenerate hypergeometric system consisting of two third-order partial differential equations. A variety of properties of system solution were considered, which shows that these solutions have the properties of generalized hypergeometric functions.